Tween 20 Stabilized Conventional Heavy Crude Oil-In-Water Emulsions Formed by Mechanical Homogenization - Shen, Wanhua; Koirala, Narayan; Mukherjee, Debjani; Lee, Kenneth; Zhao, Min; Li, Jianbing (Frontiers in Environmental Science, 2022)
This study investigated the preparation of stable conventional heavy crude oil-in-water (O/W) emulsions by mechanical homogenization with the addition of a non-ionic surfactant, Tween-20. A four-factor, five-level central composite design was carried out to investigate the effects of four independent variables, including mixing intensity (4 000-10 000 rpm), mixing duration (5-45 min), water salinity (0-40 g/L), and the concentration of emulsifier (0.1-2.1 wt.%) on the emulsion stability. Emulsion stability was determined by quantification of creaming index, turbidity change rate, and average oil droplet size. The results demonstrated that the salinity of 30 g/L, mixing intensity of 8 500 rpm, mixing duration of 35 min, and emulsifier concentration of 1.6 wt.% led to the formation of the most stable emulsion.